If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(x)=5(2-x)
We move all terms to the left:
-6(x)-(5(2-x))=0
We add all the numbers together, and all the variables
-6x-(5(-1x+2))=0
We calculate terms in parentheses: -(5(-1x+2)), so:We get rid of parentheses
5(-1x+2)
We multiply parentheses
-5x+10
Back to the equation:
-(-5x+10)
-6x+5x-10=0
We add all the numbers together, and all the variables
-1x-10=0
We move all terms containing x to the left, all other terms to the right
-x=10
x=10/-1
x=-10
| 4x-1.5=3x+0.5 | | 6r+2=-4 | | -5(3-3r)+3(-4r+8)=21 | | -0.08x=5.6. | | -x+9=5x+33 | | 7(z-79)=56 | | 3.2x-1.75.5=10 | | x+1=9x-16=87 | | 1x+3=11-3x | | 2x-3-x+9=180 | | 96=-4(8-4x) | | 5x-3+2x=3x+17 | | 14v+2=30 | | (2x+7)=(4x−17) | | -53-y/7=61 | | 2n+5+3n=4-6n+8 | | 0=v4-1 | | 3(x+2)-5=5x-2 | | 7y-3y-10=63.48 | | 7x-22+2x+38=62 | | 0.2x-12.4+1.6x+4.4=28 | | -10+10r=2r+4+2 | | (2x+5)/3(4-x)/4=3/4 | | z/5-26=-4 | | 7/19=n/19 | | 3-t=3/5 | | -15-3x=5x-2x | | 7x-22+2x+38=124 | | 6n-7=3n+8 | | -3/5+z=2/4 | | 2/5(x-17)=26 | | 12+5x=16+4x |